Peran Lingkungan Kerja dalam Meningkatkan Kinerja Karyawan: Sebuah Tinjauan Bibliometrik - Abdurrafi, Muhammad Rizky (Jurnal Manajemen, 2024)
This study aims to examine the role of the work environment in improving employee performance through a bibliometric analysis of scientific literature published between 1991 and 2024. The relationship between workplace conditions and employee productivity is explored using a systematic approach based on data extracted from the Scopus database. The research methodology applies a comprehensive bibliometric analysis utilizing VOSviewer software to map and analyze 105 scientific documents. The literature search focused on the keywords "Work Environment" and "Employee Performance," addressing the evolution of research in this field. The analysis results reveal a substantial increase in the number of publications discussing the link between the work environment and employee performance. Scientific articles dominate 70.4% of total publications, indicating a strong empirical research foundation. This finding suggests that workplace flexibility has become a crucial factor in modern organizations. The implementation of flexible work policies has proven effective in reducing employee turnover rates and increasing productivity. Furthermore, the study identifies three interconnected main clusters: human resource development, performance elements, and compensation systems, which collectively form the foundation for optimizing the work environment. The research highlights the importance of a holistic approach in creating a supportive work environment by considering both physical and psychological aspects to enhance overall organizational performance. These findings contribute to the development of more effective human resource management strategies in the contemporary era.